2006
DOI: 10.1111/j.1550-7408.2006.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Vairimorpha disparis n. comb. (Microsporidia: Burenellidae): A Redescription and Taxonomic Revision of Thelohania disparis Timofejeva 1956, a Microsporidian Parasite of the Gypsy Moth Lymantria dispar (L.) (Lepidoptera: Lymantriidae)

Abstract: Investigation of pathogens of populations of the gypsy moth, Lymantria dispar (L.) in Central and Eastern Europe revealed the existence of a microsporidium (Fungi: Microsporidia) of the genus Vairimorpha. The parasite produced three spore morphotypes. Internally infective spores are formed in the gut and adjacent muscle and connective tissue; single diplokaryotic spores and monokaryotic spores grouped by eight in sporophorous vesicles develop in the fat body tissues. The small subunit rDNA gene sequences of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 27 publications
0
32
1
Order By: Relevance
“…The early taxonomy of these microsporidia was unclear partially due to unknown spore dimorphism. More recent analyses have clarified taxonomic placements with four species, Nosema lymantriae (includes two isolates), Nosema portugal, Endoreticulatus schubergi, and Vairimorpha disparis, being the subject of transmission and host specificity studies to assess their biological control potential (Solter et al 1997;Vávra et al 2006;Solter & Hajek 2009;Solter et al 2012). Determining the identity of the various microsporidia reported to infect gypsy moth was critical for providing a link to early research with contemporary studies and to accurately identify relevant species.…”
Section: Gypsy Moth: Nosema Lymantriae and Vairimorpha Disparismentioning
confidence: 99%
See 1 more Smart Citation
“…The early taxonomy of these microsporidia was unclear partially due to unknown spore dimorphism. More recent analyses have clarified taxonomic placements with four species, Nosema lymantriae (includes two isolates), Nosema portugal, Endoreticulatus schubergi, and Vairimorpha disparis, being the subject of transmission and host specificity studies to assess their biological control potential (Solter et al 1997;Vávra et al 2006;Solter & Hajek 2009;Solter et al 2012). Determining the identity of the various microsporidia reported to infect gypsy moth was critical for providing a link to early research with contemporary studies and to accurately identify relevant species.…”
Section: Gypsy Moth: Nosema Lymantriae and Vairimorpha Disparismentioning
confidence: 99%
“…Vairimorpha disparis (=Vairimorpha sp., see Vávra et al 2006) is often isolated from L. dispar in Eastern Europe. Infection in L. dispar begins in the midgut muscles and subsequently spreads to the hemolymph, then to target tissues that include the fat body and silk glands (Solter & Maddox 1998b).…”
Section: Glyptapanteles Liparidis (Hymenoptera: Braconidae)mentioning
confidence: 99%
“…At the same time, differences in development, morphology, and ultrastructure can suggest possible taxonomic lines. As a result, a number of studies with Microsporidia are now including both ultrastructural and comparative rDNA sequence characters (Maddox et al 1999;Fries et al 1999;Andreadis and Vossbrinck 2002;Sokolova et al 2003;Vavra et al 2006). Ultrastructural morphology in addition to phylogenetic analysis using SSU-rRNA genes has been shown to be very useful in microsporidian taxonomy and phylogeny (Maddox et al 1999;Andreadis and Vossbrinck 2002;Canning et al 2002;Sokolova et al 2003).…”
Section: Molecular Analysismentioning
confidence: 98%
“…Small subunit rDNA sequence data have revealed that some of the developmental features and ultrastructural characters used to designate microsporidian taxa are the result of convergent evolution. As a result, a number of studies with Microsporidia are now including both ultrastructural and comparative rDNA sequence characters (Maddox et al 1999;Fries et al 1999;Andreadis and Vossbrinck 2002;Sokolova et al 2003;Vavra et al 2006), and eventually, with the help of phylogenetic analysis, the pattern of ultrastructural changes over evolutionary time will be determined.…”
Section: Introductionmentioning
confidence: 99%
“…These included N. ceranae and N. apis, both of which cause significant disease in honeybees (1); Vairimorpha disparis, which also belongs to the Nosema clade (32) and is a parasite studied for biological control of the gypsy moth (5); and parasites from two additional unrelated clades, Paranosema whitei, which is a parasite of flour beetles (33), and Thelohania contejeani, which causes porcelain disease in crayfish (34). The protocol described above was used.…”
mentioning
confidence: 99%